2010
DOI: 10.1007/s12010-010-9090-1
|View full text |Cite
|
Sign up to set email alerts
|

Plantlet Regeneration from Callus Cultures of Selected Genotype of Aloe vera L.—An Ancient Plant for Modern Herbal Industries

Abstract: Aloe vera L., a member of Liliaceae, is a medicinal plant and has a number of curative properties. We describe here the development of tissue culture method for high-frequency plantlet regeneration from inflorescence axis-derived callus cultures of sweet aloe genotype. Competent callus cultures were established on 0.8% agar-gelled Murashige and Skoog's (MS) basal medium supplemented with 6.0 mg l⁻¹ of 2,4-dichlorophenoxyacetic acid (2,4-D) and 100.0 mg l⁻¹ of activated charcoal and additives (100 mg l⁻¹ of asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
3
24
1
Order By: Relevance
“…Explants from greenhouse grown plants were easier to establish in cultures than the explants obtained from field grown plants and this also minimized the percentage contaminations. This is in consonance with our earlier reports (Singh et al, 2009;Rathore, Chikara, & Shekhawat, 2011) on the establishment of aloe tissue culture; Arya, Shekhawat and Singh (2003); and Rathore and Shekhawat (2009) who found that greenhouse grown plants are better source of explants. Initially, cut ends of nodal stem segments, and subsequently whole explants turned brown in color, and released phenolic compounds into the medium which adversely affected culture establishment.…”
Section: Plant Materials and Culture Establishmentsupporting
confidence: 92%
See 1 more Smart Citation
“…Explants from greenhouse grown plants were easier to establish in cultures than the explants obtained from field grown plants and this also minimized the percentage contaminations. This is in consonance with our earlier reports (Singh et al, 2009;Rathore, Chikara, & Shekhawat, 2011) on the establishment of aloe tissue culture; Arya, Shekhawat and Singh (2003); and Rathore and Shekhawat (2009) who found that greenhouse grown plants are better source of explants. Initially, cut ends of nodal stem segments, and subsequently whole explants turned brown in color, and released phenolic compounds into the medium which adversely affected culture establishment.…”
Section: Plant Materials and Culture Establishmentsupporting
confidence: 92%
“…The use of antioxidant additives such as citric acid and ascorbic acid is essential at least during the cultures establishment; and may or may not be included during proliferation of cultures. These kinds of treatments have been proved to be beneficial in our previous report (Singh et al, 2009;Rathore et al, 2011) and are in consonance with Arya and Shekhawat (1986) and Poudyal, Guoqiang, Yuxing, Jie, & Qingchun (2008).…”
Section: Plant Materials and Culture Establishmentsupporting
confidence: 55%
“…Vyas University, Jodhpur served as source of explants. Efficient plantlet regeneration both through direct shoot bud proliferation without callus phase (protocol 1) using axillary shoot buds [10] and indirect shoot bud proliferation via intermediate callus phase (protocol 2) using soft base of inflorescence axis as an explant [11] was achieved. Figure 1 shows a schematic representation of different steps of protocols and Murashige and Skoog's basal medium [22] with plant growth regulators used for plantlet regeneration.…”
Section: Methodsmentioning
confidence: 99%
“…Efficient plantlet regeneration for a selected genotype of A. vera L. sweet aloe was achieved through direct shoot bud proliferation using axillary shoot buds [10] and indirect shoot bud regeneration via an intervening callus phase using inflorescence axis as explants [11]. Plant tissue culture techniques are of extensive uses where quality material of a selected genotype is required at mass scale, for commercial cultivation and the natural propagation do not meet the required demands.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro propagation can be pursued through axillary bud stimulation and through de novo in vitro organogenesis (Rathore et al, 2011a,b; Gupta et al, 2014; Kanwar et al, 2015). In order to achieve a satisfactory production of healthy and standardized plantlets, the various stages of the in vitro cloning of A. vera need to be optimized.…”
Section: Propagation Techniquesmentioning
confidence: 99%